Performances of Hydrated Cement Treated Crushed Rock Base for Western Australian Roads - Chummuneerat, Suphat; Jitsangiam, Peerapong; Nikraz, Hamid (International Society for Asphalt Pavements (ISAP), 2012)
This paper presents the resilient modulus (MR) of Hydrated Cement Treated Crushed Rock Base (HCTCRB) affected by amount of hydration periods, compaction processes and dryback using the repeated load triaxial tests. The related trends of MR correspond to the different hydration periods still cannot be concluded. Instead, It was found that the moisture content play more major influence on the MR performance. Higher additional water during compaction of HCTCRB, even at its OMC and induced higher dry density, led to the inferior MR performance compared to the sample without water addition. The MR of damper samples could be improved through dryback process and superior to that of the sample without water addition at the same moisture content. However, the samples without water addition during compaction delivered the comparable MR values even its dry density was lower than the other two types. These results indicated the significant influence of moisture content to the performances of HCTCRB with regardless of the dry density. Finally, the experimental results of HCTCRB and parent material were evaluated with the K-? model and the model recommended by Austroads. These two models provided the excellent fit of the tested results with high degree of determination (R2).